Integrated Strategies for Air Quality and Thermal Comfort Improvement: The Case Study of the University Campus of Catania - Salvatore Leonardi; Maurizio Detommaso; Nilda Georgina Liotta; Natalia Distefano; Francesco Nocera; Vincenzo Costanzo (Applied Sciences)
Urban campuses face critical environmental challenges due to high pedestrian density, traffic-induced air pollution, and thermal stress, especially in compact Mediterranean settings. These conditions can compromise the usability and livability of outdoor spaces. This study investigates whether greening and material-based interventions can offset a lower degree of traffic reduction in improving air quality and thermal comfort. The University Campus of Catania (Southern Italy) served as the case study. An integrated microscale simulation framework using ENVI-met was developed, calibrated, and validated with local traffic, meteorological data, and field measurements of PM10 and PM2.5. Three scenarios were tested: a baseline, Scenario 1 (50% traffic reduction with moderate greening), and Scenario 2 (30% traffic reduction with more extensive greening and material interventions). Results showed that Scenario 1 consistently outperformed Scenario 2 in all pedestrian hotspots. The highest reductions recorded in Scenario 1 were −0.150 μg/m3 for PM2.5 (−11.5%), −0.069 μg/m3 for PM10 (−5.9%), −2.16 °C for UTCI (−7.6%), and −2.52 °C for MRT (−4.5%). These findings confirm that traffic reduction is the dominant factor in achieving environmental improvements, although greening and innovative materials play a valuable complementary role. The study supports integrated planning strategies for climate-responsive and healthier university environments.